Relación Del Liderazgo Transformacional Y El Clima Organizacional En El Personal Docente Y Administrativo De La Universidad Privada Telesup Chiclayo 2017 - Carpio Vásquez, Weiky Nelly Juliana (2018)
De acuerdo a los estudios realizados y las teorías modernas de liderazgo y el comportamiento humano, el éxito de las organizaciones, depende de los administradores gerentes o líderes, quienes tienen la difícil tarea de conducirla hacia el logro de las metas propuestas. Por otro lado, es necesario considerar que en toda organización existe un elemento que va a condicionar la consecución de las metas trazadas. Este elemento es el denominado clima organizacional. En virtud del contexto descrito, la investigación desarrollada en la presente, tuvo como propósito establecer la relación del liderazgo transformacional y el clima organizacional en el personal docente y administrativo de la Universidad privada TELESUP, Chiclayo 2017. En ese sentido el problema identificado en la investigación se formuló mediante la siguiente interrogante: ¿Cómo se relaciona el Liderazgo transformacional y el Clima organizacional en el personal docente y administrativo de la Universidad Privada Telesup Chiclayo 2017? Teniendo como Objetivo General: Determinar la relación que existe entre el Liderazgo transformacional y el Clima organizacional en el personal docente y administrativo de la Universidad Privada TELESUP Chiclayo 2017. Para tal investigación se asumió como hipótesis: El Liderazgo transformacional se relaciona significativamente con el Clima organizacional en el personal docente y administrativo de la Universidad Privada TELESUP Chiclayo 2017. Las variables de estudio son: Variable Independiente (VI): Liderazgo Transformacional y la Variable Dependiente (VD): Clima Organizacional El tipo de investigación es cualitativo – descriptivo, no experimental, inductivo, corte transversal, no probabilístico. Se trabajó con una población muestral de 65 personas (docentes y administrativos), que laboran en la Universidad TELESUP Chiclayo. Con instrumentos de medida y para la recolección de datos, nos valimos de la observación y encuesta. La encuesta contuvo 20 preguntas debidamente estructuradas, la misma que fue evaluada por expertos. Luego se hizo la tabulación y evaluación estadística de cada una de las preguntas, hasta terminar representándose gráficamente en cada uno de los estadígrafos. Los hallazgos en el presente estudio permitieron llegar a la conclusión que si existe relación significativa entre el Liderazgo transformacional y el clima organizacional en en el personal docente y administrativo de la Universidad Privada TELESUP Chiclayo 2017. According to the studies carried out and the modern theories of leadership and human behavior, the success of the organizations depends on the managing managers or leaders, who have the difficult task of leading it towards the achievement of the proposed goals. On the other hand, it is necessary to consider that in every organization there is an element that will condition the achievement of the goals set. This element is the so-called organizational climate. In view of the described context, the research developed in this one, had as purpose to establish the relation of the transformational leadership and the organizational climate in the teaching and administrative personnel of the private University TELESUP, Chiclayo 2017. In this sense, the problem identified in the research was formulated by means of the following question: How does the transformational leadership and the organizational climate relate to the teaching and administrative staff of the Private University Telesup Chiclayo 2017? Having as General Objective: To determine the relationship that exists between the transformational Leadership and the organizational Climate in the teaching and administrative personnel of the Private University TELESUP Chiclayo 2017. For such research it was assumed as a hypothesis: The transformational leadership is significantly related to the organizational climate in the teaching and administrative staff of the Private University TELESUP Chiclayo 2017. The study variables are: Independent Variable (VI): Transformational Leadership and the Dependent Variable (VD): Organizational Climate. The type of research is qualitative - descriptive, not experimental, inductive, cross section, not probabilistic. We worked with a sample population of 65 people (teachers and administrators), who work at the TELESUP Chiclayo University. With measurement instruments and for data collection, we use observation and survey. The survey contained 20 properly structured questions, the same one that was evaluated by experts. Then the tabulation and statistical evaluation of each of the questions was done, until it was graphically represented in each of the statisticians. The findings in this study allowed us to conclude that there is a significant relationship between the transformational leadership and the organizational climate in the teaching and administrative staff of the Private University TELESUP Chiclayo 2017. We emphasize that in the Private University TELESUP - Chiclayo there is no transformational leadership, because the director of this institution does not project a strong vision and personality, capable of changing expectations, perceptions and motivations, to orient them towards an adequate organizational climate in the institution. In addition, there is no evidence of a process based on an adequate relationship between the director and the staff, which generates trust, respect and mutual admiration.